Management accounting systems in Finnish service firms - Hussain, Md. Mostaque (Technovation)
Based on a study of thirty-two Finnish service firms in late 1993, the authors found that Management Accounting System such as Activity Based Costing (ABC) were not frequently used, even though they would be helpful in appreciating real production costs.